ANALYSIS OF THE UTILIZATION OF VILLAGE FUND IN POVERTY ALLEVIATION IN WAJO REGENCY DURING THE COVID-19 PANDEMIC (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to describe and analyze the usage and utilization of village funds in povertyalleviation, the village fund cash block grants sourced from village funds in helping poor andincapable households, and the level of their acceptance of village fund cash block grants affectedby the Covid-19 Pandemic.A mixed approach (qualitative and quantitative) was utilized as amethodology with a case study research strategy. Data was collected through interviews,observations, questionnaires, and document review. Informants selected by purposive samplingconsisted of actors from local government officials, sub-district government officials, villagegovernment officials, members of the village consultative body, community leaders, NGOs,academics, members of the poor households.Furthermore, the usage of village funds has notsignificantly contributed to the poverty alleviation rate in rural areas. In the implementation ofcash block grants from village funds for poor and incapable households are determined based onseveral dimensions such as: resulting in the appropriate criteria, lacking updating data in datacollection, reporting and accountability, coaching and monitoring, providing complaint channelscarried out by central and regency government policies.